The Impact of Double Date Events, Flash Sales, and Free Shipping on Impulsive Buying Behavior: A Study of Shopee Using University Students in Surabaya - Intan Mitayani; Budi Prabowo (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the influence of twin date events, flash sales, and free shipping promotions on impulsive buying behavior among university students who use the Shopee application in Surabaya. The rise of promotional activities in e- commerce, particularly during twin date events, has contributed to a growing trend of unplanned or impulsive purchases, especially among young consumers. This research employs a quantitative associative approach. The sampling technique used is purposive sampling, involving 100 student respondents who have shopping experience on Shopee. Data were collected through questionnaires and analyzed using multiple linear regression with SPSS software. The results show that twin date events, flash sales, and free shipping promotions simultaneously have a significant effect on impulsive buying behavior. Partially, each independent variable also significantly influences impulsive purchases. These findings indicate that Shopee's marketing strategies—based on time-limited promotions and cost incentives—are effective in stimulating impulsive buying among students. This research contributes both theoretically and practically to the understanding of consumer behavior in the digital era.